The Latency-Associated Transcript Inhibits Apoptosis via Downregulation of Components of the Type I Interferon Pathway during Latent Herpes Simplex Virus 1 Ocular Infection - Tormanen, Kati (J Virol, 2019)
The herpes simplex virus (HSV-1) latency-associated transcript (LAT) has been shown to inhibit apoptosis via inhibiting activation of proapoptotic caspases. However, the mechanism of LAT control of apoptosis is unclear, because LAT is not known to encode a functional protein, and the LAT transcript is found largely in the nucleus. We hypothesized that LAT inhibits apoptosis by regulating expression of genes that control apoptosis. Consequently, we sought to establish the molecular mechanism of antiapoptosis functions of LAT at a transcriptional level during latent HSV-1 ocular infection in mice. Our results suggest the following. (i) LAT likely inhibits apoptosis via upregulation of several components of the type I interferon (IFN) pathway. (ii) LAT does not inhibit apoptosis via the caspase cascade at a transcriptional level or via downregulating Toll-like receptors (TLRs). (iii) The mechanism of LAT antiapoptotic effect is distinct from that of the baculovirus inhibitor of apoptosis (cpIAP) because replacement of LAT with the cpIAP gene resulted in a different gene expression pattern than in either LAT(+) or LAT(−) viruses. (iv) Replacement of LAT with the cpIAP gene does not cause upregulation of CD8 or markers of T cell exhaustion despite their having similar levels of latency, further supporting that LAT and cpIAP function via distinct mechanisms. IMPORTANCE The HSV-1 latency reactivation cycle is the cause of significant human pathology. The HSV-1 latency-associated transcript (LAT) functions by regulating latency and reactivation, in part by inhibiting apoptosis. However, the mechanism of this process is unknown. Here we show that LAT likely controls apoptosis via downregulation of several components in the JAK-STAT pathway. Furthermore, we provide evidence that immune exhaustion is not caused by the antiapoptotic activity of the LAT.